Disabilitas dan Keselamatan Pasien : Studi Literatur - Dhamanti, Inge; Larasati, Andriyani (Jurnal Kesehatan Komunitas, 2024)
Improving the safety of vulnerable patient groups in health care is a priority. Patients with disabilities are among the most vulnerable groups. Persons with disabilities have more complex and extensive healthcare needs than non-disabled patients. This literature review aims to identify the types of patient safety incidents that can be used in patients with disabilities. The keywords "patient safety" and "disability" were used to search the Pubmed and Google Scholar databases for articles. The final results revealed four articles that met the inclusion criteria. The findings revealed that patients with disabilities are still frequently subjected to patient safety incidents such as falls, medication errors, infections, burns, and fluid leaks beneath the skin. According to the findings of the analysis using the Donabedian framework, there are still many problems that occur in structural components and processes, which can have an impact on the results obtained. Because of their vulnerability and uniqueness, patients with disabilities are more vulnerable to patient safety incidents. Furthermore, the issue of disability and patient safety remains the primary concern, so studies on disability and patient safety are still limited.